Photoresponses of Light-Grown phyA Mutants of Arabidopsis (Phytochrome A Is Required for the Perception of Daylength Extensions). - Johnson, E; Bradley, M; Harberd, N; Whitelam, G (1994)
Several aspects of the photophysiology of wild-type Arabidopsis thaliana seedlings were compared with those of a phytochrome A null mutant, phyA-1, and a mutant, fhy1, that is putatively involved in the transduction of light signals from phytochrome A. Although phyA seedlings display a near wild-type phenotype when grown in white light (W), they nevertheless display several photomorphogenic abnormalities. Thus, whereas the germination of wild-type and fhy1 seeds is almost fully promoted by a pulse of red light (R) or by continuous far-red light (FR), phyA seed germination is responsive only to R. Following growth under day/night cycles, but not under continuous W, the hypocotyls of light-grown phyA and fhy1 seedlings are more elongated than those of wild-type seedlings. For seedlings grown under low red/far-red (R/FR) ratio light conditions, phyA and fhy1 seedlings display a more marked promotion of hypocotyl elongation than wild-type seedlings. Similarly, seedlings that are doubly null for phytochrome A and phytochrome B(phyA phyB) also have more elongated hypocotyls under low R/FR ratio conditions than phyB seedlings. This indicates that phytochrome A action in light-grown seedlings is antagonistic to the action of phytochrome B. Although wild-type, fhy1, and phyA seedlings flower at essentially the same time under both short-day and long-day conditions, an obvious consequence of phytochrome A deficiency is a pronounced late flowering under conditions where a short day of 8 h of fluorescent W is extended by 8 h of low-fluence-rate incandescent light. The evidence thus indicates that phytochrome A plays a role in seed germination, in the control of elongation growth of light-grown seedlings, and in the perception of daylength.